Analysis of current-in-plane giant magnetoresistance using Co2FeAl0.5Si0.5 half-metallic Heusler alloy. (23rd December 2021) - Fathoni, Kresna B; Sakuraba, Yuya; Miura, Yoshio; Sasaki, Taisuke; Nakatani, Tomoya; Hono, Kazuhiro
Abstract: There has been renewed interest in current-in-plane giant magnetoresistance (CIP-GMR) devices for high-sensitivity magnetic sensors. However, further improvement in magnetoresistance (MR) ratio is necessary to achieve sufficient magnetic field sensitivity. Use of a half-metallic Co-based Heusler alloy ferromagnetic (FM) layer has been demonstrated to be effective in enhancing GMR in the configuration with current perpendicular to the plane; however, only small MR ratios are obtained in the CIP configuration. To understand the origin of the disappointingly low MR in the CIP configuration when using Heusler alloy FM layers, we investigated the magnetotransport properties of CIP-GMR devices using half-metallic Co2 FeAl0.5 Si0.5 (CFAS) Heusler alloy and conventional CoFe alloy as the FM layers in combination with Ag or Cu as a nonmagnetic (NM) spacer layer. Regardless of the high lattice and electronic band matching at the CFAS/Ag interface, CFAS/Ag CIP spin valves (SVs) show a MR ratio of only 1.2% at room temperature, which is much smaller than those of reference CoFe/Cu and CoFe/Ag SVs (21.6% and 8.4%, respectively). Current density distribution simulations suggest that large current shunting occurs in the Ag layer due to the significant resistivity gap between CFAS and Ag, which limits the generation of highly spin-polarized current from the CFAS layer, resulting in the very small MR ratios. To enhance the MR ratio in CIP-GMR using half-metallic materials, resistivity matching between FM layers and the NM layer is required, in addition to the high electronic band match that has been considered, as a key factor to obtain a high MR ratio in CIP-GMR devices.